Lysophosphatidic acid does not cause blood/lymphatic vessel plasticity in the rat mesentery culture model. Issue 13 (8th July 2016) - Sweat, Richard S.; Azimi, Mohammad S.; Suarez‐Martinez, Ariana D.; Katakam, Prasad; Murfee, Walter L.
Abstract: Understanding the mechanisms behind endothelial cell identity is crucial for the goal of manipulating microvascular networks. Lysophosphatidic acid (LPA) and serum stimulation have been suggested to induce a lymphatic identity in blood endothelial cells in vitro. The objective of this study was to determine if LPA or serum induces blood‐to‐lymphatic vessel phenotypic transition in microvascular networks. The rat mesentery culture model was used to observe the effect of stimulation on blood and lymphatic microvascular networks ex vivo. Vascularized mesenteric tissues were harvested from adult Wistar rats and cultured with LPA or 10% serum for up to 5 days. Tissues were then immunolabeled with PECAM to identify blood vessels and LYVE‐1 or Prox1 to identify lymphatic vessels. We show that while LPA caused capillary sprouting and increased vascular length density in adult microvascular networks, LPA did not cause a blood‐to‐lymphatic phenotypic transition. The results suggest that LPA is not sufficient to cause blood endothelial cells to adopt a lymphatic identity in adult microvascular networks. Similarly, serum stimulation caused robust angiogenesis and increased lymphatic/blood vessel connections, yet did not induce a blood‐to‐lymphatic phenotypic transition. Our study highlights an understudied area of lymphatic research and warrants future investigation into the mechanisms responsible for the maintenance of blood and lymphatic vessel identity. Abstract : An emerging area of microvascular research is focused on lymphatic/blood vessel mispatterning and plasticity. Our results caution the translation of cell culture‐based studies to an adult network scenario, in which blood/lymphatic endothelial cell phenotypic transition requires a more complicated milieu of signals.